Chapter 3 Artistic Research: Defining the Field - Butt, Danny (Intellect, 2017)
The rapid growth of doctoral-level art education challenges traditional ways of thinking about academic knowledge, and yet, as Danny Butt argues in this book, the creative arts may also represent a positive blueprint for the future of the university. Synthesizing institutional history with aesthetic theory, Artistic Research in the Future Academy reconceptualizes the contemporary crisis in university education toward a valuable renewal of creative research.